2020
DOI: 10.5937/ffr47-28435
|View full text |Cite
|
Sign up to set email alerts
|

By-products of the oil industry as sources of amino acids in feed

Abstract: A global increase in the demand for livestock products suggests that there will be a consequent rise in demand for feed, not only of cereals but of other feeds and particularly proteins. In the present study, oil industry by-products such as soybean meal, soybean cake and sunflower meal were analysed as sources of amino acids in animal nutrition. From among oilseed byproducts, the soybean meal content the most of crude protein up to 44% and the best of amino acid composition, while content of crude cellulose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…The total content of nonessential amino acids (aspartic acid, serine, glutamic acid, proline, glycine, alanine, cystine, tyrosine, and arginine) was 57.86 g 100g −1 and made up 65.67% of the total amino acids (Figure 5a). Similar results were obtained by Siddiqi et al [33] and Tomičić et al [64]. The aforementioned amino acids are linked to gluten proteins (gliadin and glutenin) and play an important role in the end-product use of wheat flour [33].…”
Section: Nonessential Amino Acid Contentsupporting
confidence: 80%
See 1 more Smart Citation
“…The total content of nonessential amino acids (aspartic acid, serine, glutamic acid, proline, glycine, alanine, cystine, tyrosine, and arginine) was 57.86 g 100g −1 and made up 65.67% of the total amino acids (Figure 5a). Similar results were obtained by Siddiqi et al [33] and Tomičić et al [64]. The aforementioned amino acids are linked to gluten proteins (gliadin and glutenin) and play an important role in the end-product use of wheat flour [33].…”
Section: Nonessential Amino Acid Contentsupporting
confidence: 80%
“…The essential amino acids, which included threonine, histidine, valine, methionine, phenylalanine, isoleucine, leucine, and lysine, accounted for 34.34% of the total amino acids (Figure 6a). This is confirmed by the results established by Siddiqi et al [33] and Tomičić et al [64]. The highest content of total essential amino acids was found in genotypes approved in the 1980s, such as Agrounija (32.62 g 100 g −1 protein) and Tanjugovka (32.47 g 100 g −1 protein), whereas genotype Orašanka, approved in the 1970s, had the lowest content (28.54 g 100 g −1 protein).…”
Section: Essential Amino Acid Contentsupporting
confidence: 77%
“…The use of non-traditional types of raw materials in the production of compound feed for valuable fish species, modes of production technology of experimental compound feed by the extrusion method and its storage terms were considered in [17]. It was found that the most promising sources of raw materials for valuable types of fish were soybeans, pea isolates and concentrates, wheat and corn gluten, meal and cake (soybean, flaxseed, rapeseed).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The amino acid peaks were identified by comparison of retention times with retention times of amino acid standard purchased from Sigma Aldrich (Amino Acid Standard Solution (Sigma-Aldrich, St. Louis, USA)). The results were expressed as mass of amino acid (g) in 100 g of sample (Tomičić et al, 2020). The weight of cereal samples was uniform in terms of dry matter before the amino acid analyzes.…”
Section: Analysis Of Amino Acid Compositionmentioning
confidence: 99%